2018
DOI: 10.1186/s12951-017-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Ready-to-use protein G-conjugated gold nanorods for biosensing and biomedical applications

Abstract: BackgroundGold nanorods (GNRs) display unique capacity to absorb and scatter near infrared light, which arises from their peculiar composition of surface plasmon resonances. For this reason, GNRs have become an innovative material of great hope in nanomedicine, in particular for imaging and therapy of cancer, as well as in photonic sensing of biological agents and toxic compounds for e.g. biomedical diagnostics, forensic analysis and environmental monitoring. As the use of GNRs is becoming more and more popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
3
14
0
Order By: Relevance
“…The role of thiolated PEG is particularly critical as well. PEG is the most standard coating to gain colloidal stability in physiological fluids [75, 83–85]. Here, we found that its use also grants substantial chemical stability.…”
Section: Resultsmentioning
confidence: 87%
“…The role of thiolated PEG is particularly critical as well. PEG is the most standard coating to gain colloidal stability in physiological fluids [75, 83–85]. Here, we found that its use also grants substantial chemical stability.…”
Section: Resultsmentioning
confidence: 87%
“…Protein G was experimented with immunoconjugation antibodies to gold–gold sulfide nanoparticles in photothermal cancer therapy [ 37 ]. Centi and colleagues utilized protein G with gold nanorods for potential use in biosensing in nanomedicine [ 38 ]. Furthermore, in relation to the present study, previous works demonstrated that chondrocytes can be successfully coated with antibodies to chondroitin 4-sulfate and type II collagen via protein G [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…their size, shape, state of aggregation and environment 3 , 6 , 7 . It is relatively simple to modify their surface with functional biomolecules like proteins 8 , 9 , such as antibodies 10 , 11 and enzymes 12 , 13 , aptamers 14 , 15 , other oligonucleotides 16 , 17 , or polysaccharides 18 20 . Relevant methods include protocols for both passive absorption (i.e.…”
Section: Introductionmentioning
confidence: 99%